Peran Perpustakaan dalam Menunjang Proses Belajar Mengajar Siswa dan Tenaga Pendidik di Madrasah Ibtidaiyah Negeri 2 Madiun - Putri, Widya; Nasrullah; Majidah; Hermawan, Nanang; Hidayatullah, Fauzan; Tawakkal; Akbar, Azaz (Literatify: Trends in Library Developments, 2025)
This research aims to determine the efforts made by the State Madrasah Ibtidaiyah 2 Madiun Library as well as the obstacles faced in supporting the teaching and learning process of students and educators at the school. This study employs a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the efforts made by the State Madrasah Ibtidaiyah 2 Madiun Library, which plays a supporting role in the teaching and learning process of students and educators, include library promotion activities, implementing a book rolling program, mandatory library visits, providing teaching aids as learning support, offering e-book services, and providing special collections for teachers. The obstacles faced by the library in supporting the learning process of students and educators include limited break time and the tendency of students to prefer using gadgets over reading physical books. Despite these challenges, it is hoped that the State Madrasah Ibtidaiyah 2 Madiun Library will innovate by implementing more engaging activities, such as educational games, to attract students and encourage them to utilize the facilities available at the library.